Enhancing sustainable urban mobility in Pakistan through renewable hydrogen integration and policy interventions - Rana Muhammad Amir Latif (Discover Cities)
Abstract This study explores strategies to enhance sustainable urban mobility in Pakistan, particularly emphasizing integrating renewable hydrogen energy and the role of policy interventions in reducing carbon emissions. As cities evolve, adopting sustainable transportation solutions becomes increasingly critical to meet environmental goals. This paper identifies key challenges and opportunities for transforming Pakistan’s transportation sector into a more sustainable, low-carbon system. A multi-stage stratified sampling approach was used to gather insights from 1200 respondents across Pakistan’s five provinces: Punjab, Sindh, Khyber Pakhtunkhwa, Balochistan, and Islamabad. The survey assessed perceptions of government support, infrastructure adequacy, affordability, and environmentally sustainable transport options. This paper thus presents a timely study aimed at enhancing the knowledge base in support of renewable hydrogen and sustainable urban mobility in Pakistan. Findings highlight the transformative potential of renewable hydrogen in de-carbonizing the transportation sector and underscore the critical role of strategic policy frameworks in overcoming existing barriers. This study contributes to developing sustainable urban mobility policies in Pakistan, offering insights into how renewable hydrogen can support broader environmental and development goals for future cities.